EFFECTS OF THE VIBRATION PLATFORM ON THE NEUROMUSCULOSKELETAL SYSTEM IN PATIENTS WITH PARKINSON’S DISEASE: LITERATURE REVIEW - Santos, Luís Rodolfo Teixeira dos; Carvalho, Gilberto Eusébio de; Costa, Davidson Ribeiro; Pessoa, Diego Rodrigues (Journal of Health Care, 2018)
Introduction: Parkinson’s disease (PD) is a neurodegenerative condition that causes limitations and incapacities in its bearers. Objective: This study aimed to perform a literature review about the effects of the vibration platform on the musculoskeletal system of PD patients. Materials and methods: The study was based on the research of papers published in PubMed/MedLine, LiLacs and Scielo databases, between January 2011 and January 2017, combining descriptors "Parkinson’s disease", "vibration platform", and "benefits" with the Boolean descriptors in the mentioned sources. Twenty-three articles were found in this study; thereafter the inclusion and exclusion criteria were applied, and only eight of them were included. Results: It should be noted that most of the aforementioned studies have demonstrated positive responses (frequencies between 3 Hz to 35 Hz), in variables such as gait, proprioception, quality of life and postural stability. Conclusion: The scientific evidence does not yet fully clarify the main physiological mechanisms for proving the vibration platform effects on Parkinson’s disease.